A threat to Canadian national security: a lesbian soldier's story. Issue 2 (3rd July 2018) - Gouliquer, Lynne; Poulin, Carmen; Moore, Jennifer
ABSTRACT: Before 1992, lesbians and gay soldiers were purged and discharged from the Canadian military for "reasons of homosexuality." Those caught or suspected of homosexuality were subject to lengthy, humiliating, and degrading interrogations. This short story sheds light on this painful past. It is based on findings of a nationally funded pan-Canadian longitudinal study examining how Canadian military policies and practices influenced the lives of lesbian, gay, bisexual, and transgender soldiers and their partners. In total, 126 people were interviewed. While in the military, countless soldiers were investigated, numerous interrogated, many lost their careers, some committed suicide and others survived. Personal details have been changed to ensure the anonymity of the people, but it is their voices that tell this story. An official state apology was delivered November 28, 2017. Due to an impending class action court case, an agreement for compensation was also reached. Compensation and memorials will be forthcoming to those who were affected by the LGBTQI2+ purge campaign. To this day, no evidence exits that these soldiers were "ever" a threat to national security.